ACUTE APPENDICITIS IN POSTPARTUM PERIOD: A DIAGNOSTIC CHALLENGE - Jankovic, Natasa; Jankovic, Milos; Lilic, Aleksandar; Djurov, Vladan; Djordjevic, Vladan (Acta medicae Medianae, 2025)
Acute appendicitis in pregnancy and the puerperium is the most common non-obstetric condition requiring urgent surgery. Unlike appendicitis during pregnancy, reports of appendicitis occurring during delivery and the early puerperium are rare. The most common puerperal infections include puerperal endometritis, urinary tract infections, adnexal torsion, tubo-ovarian abscess, ovarian vein thrombosis, sepsis, pelvic thrombophlebitis, pyelonephritis, pneumonia, and cholecystitis. Diagnosing acute appendicitis in pregnancy and the puerperium is challenging due to atypical or diminished symptoms caused by abdominal wall distension, displacement of abdominal organs, and reduced tissue response to inflammation. The primary symptoms of appendicitis during pregnancy include vomiting, anorexia, nausea, fever, and pain in the lower right abdomen or flank. Appendicitis can lead to refractory postpartum sepsis and should be considered in postpartum patients with sepsis of unknown origin, necessitating a multidisciplinary approach involving both obstetricians and surgeons.